The Influence of Group Cohesiveness on the Intentions of Spreading Fake News (Hoax) on Adulthood in Three Cities in West Java - Lova Riza, Wina; Muharsih, Lania; Heryono, Heri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine whether or not the influence of group cohesiveness on the intentions of spreading hoax in West Java. The method used in this study carried out a quantitative method, the sample used in this study were 245 people drawn from the order of the top cities in the use of social media in West Java. The technique used for sampling in this study is snowball sampling, data collection using a Likert type scale that is the scale of group cohesiveness and the scale of the intention to spread the hoax issue. The analysis in this study uses a simple linear regression analysis to determine the effect of group cohesiveness (X) on the intentions of spreading hoax (Y). Based on the results of data analysis shows that there is a strong influence of group cohesiveness on the intention of spreading hoaxes in West Java with the acquisition value of F = 166.014 with a significance of 0,000 less than 0.05 (p